Development of an Enriched Polyphenol (Natural Antioxidant) Extract from Orange Juice (Citrus sinensis) by Adsorption on Macroporous Resins. (24th February 2020) - Campone, Luca; Celano, Rita; Rizzo, Serena; Piccinelli, Anna Lisa; Rastrelli, Luca; Russo, Mariateresa
Abstract : Orange ( Citrus sinensis ) juice contains a high amount of antioxidant compounds, such as polyphenols and vitamins. The aim of this work was to develop an adsorption procedure for the quantitative recovery of polyphenols from fresh orange juice. Different macroporous resins have been selected to evaluate their affinity for phenolic compound in order to purify the antioxidant compounds from the orange juice. The main compounds of orange juice were firstly characterized using an UPLC-UV-HRMS to define the metabolite profile, and subsequently three different types of adsorbent (XAD-2, XAD-4, and XAD-16N) were tested to concentrate these bioactive compounds. The time of contact was selected based on kinetic studies, and subsequently the adsorption and elution conditions were optimized in order to maximize the recovery of phenolic compounds to obtain an extract rich of bioactive compounds. Lastly, antioxidant capacity of the orange juice extract of selected macroporous resin, obtained under optimized conditions, was determined by in vitro antioxidant assays.